2007
DOI: 10.1136/bjsm.2007.035691
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to prevent injury in adolescent sport: a systematic review

Abstract: This systematic review set out to identify randomised controlled trials and controlled intervention studies that evaluated the effectiveness of preventive strategies in adolescent sport and to draw conclusions on the strength of the evidence. A literature search in seven databases (Medline, SportDiscus, EMBASE, CINAHL, PEDro, Cochrane Review and DARE) was carried out using four keywords: adolescent, sport, injury and prevention (expanded to capture any relevant literature). Assessment of 154 papers found 12 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(88 citation statements)
references
References 51 publications
1
80
0
7
Order By: Relevance
“…Therefore, we propose that obese people should undergo weight reduction and be advised to do low-intensity exercises that improve flexibility, balance, and muscle strength. 34,35 Our study has several limitations that should be noted. First, the study uses self-reported weight and height information to determine BMI and overweight and obese individuals have been reported to under-report body weight.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, we propose that obese people should undergo weight reduction and be advised to do low-intensity exercises that improve flexibility, balance, and muscle strength. 34,35 Our study has several limitations that should be noted. First, the study uses self-reported weight and height information to determine BMI and overweight and obese individuals have been reported to under-report body weight.…”
Section: Discussionmentioning
confidence: 93%
“…Ergenlerde spor yaralanmalar›n› önleme programlar› ile pasif önleme stratejileri ve aktif önleme stratejileri protokoller dahilinde düzenlenip uyguland›¤›nda ve sporcular, antrenör ve aileler programa iyi uyum sa¤lad›¤›nda yaralanmalar›n anlaml› derecede azald›¤›n› göstermifltir (5,12,13).…”
Section: Giriflunclassified
“…[3] Young people are particularly at risk of sports injury because of high levels of exposure at a time of major physiological change. [4] The importance of injury prevention in football (IPF) among young players cannot be overemphasised as talented players need to stay injury-free as far as possible, to get to the peak of their careers. Implementation of injury-prevention measures in this extremely vulnerable population of disadvantaged youth is therefore imperative.…”
mentioning
confidence: 99%
“…[2,[4][5][6][7][8] Football players in Nigeria are faced with huge challenges. A major problem is the low level of financial resources for professional, amateur and youth clubs, most of which are not well funded, especially those owned by the government.…”
mentioning
confidence: 99%